Folk liturgies and narratives of holy wells among the Yoruba of southwest Nigeria - Raheem, Oluwafunminiyi (Array, 2021)
Building on Celeste Ray"s extensive research on Ireland"s holy wells, I show how folk liturgies underlie meanings that are closely related to some of the practices that manifest around holy wells among the Yoruba in southwest Nigeria – meanings that are often neglected in the holy wells literature. I adapt some holy wells terms as they appear in existing studies for illustrative as well as for comparative purposes. Their interpretation and analysis will, however, focus on the liturgical narratives that best fit the article"s perception of what is local to holy wells among the Yoruba. With a focus on two holy wells, Olokun and Ori Aye, the article draws on the testimonies of local knowledge, close research encounters of ritual practices and performances and readings from extant literature to open the window through which holy wells and their various manifestations in the socio-cultural life among the Yoruba could be properly assessed and adequately understood.